Digital competences for teaching and learning - Natasa Angjeleska (University American College Skopje, 2022)
This paper reflects on the data gathered from research in June 2020 on the experiences of teachers and school management during the online teaching imposed due to the COVID 19 pandemic. The research compiled data from 576 teachers, 61 principals and school support teams from 30 primary schools in urban and rural locations in the country and with 5 different languages of instruction (Macedonian, Albanian, Turkish, Serbian and Bosnian). Information gathered from the respondents of the questionnaires indicated that as many as 10.2 per cent of teachers rated online teaching with the grade "unsatisfactory", 15.8 per cent rated it as "satisfactory", and 41.7 per cent as "good". Furthermore, this research points out that the ways in which online teaching was performed varied widely among schools and among teachers, with the most common being assigning homework, applying existing platforms and sending presentations. ICT training organized by schools and the education authorities, and the equipment provided by the schools, had the least contribution in the success of teaching. On-line teaching in a time of crise revealed shortcomings in terms of teachers' competences in implementing engaging activities for students and performing different types of distance teaching methods. Although digitalization was somewhere on the agenda globally, very quickly it became a priority all over the world, including in our own country, and specifically in education.The research findings in this paper are considered in the context of The European Framework for the Digital Competence of Educators (DigCompEdu) that aims to provide a general reference framework for the developers of digital competence models and is directed towards educators at all levels of education, including general and vocational training, special needs education, and non-formal learning contexts. Even though this framework was developed and adopted in 2017, during the pandemic it showed advantages to be addressed by many educators and policy makers.
Keywords: 330; teachers; online teaching; learning; COVID 19; digital competences